Simulation and Analysis of Temperature Distribution and Material Properties Change of a Thermal Heat sink Undergoing Thermal Loading in a Mobile Computer - Xavier, A.; Lim, C. S. (IOP Publishing, 2015)
This paper is aimed at studying the thermal distribution and its associated effects on a thermal heat sink of a mobile computer (laptop). Possible thermal effects are investigated using Finite-Element Method with the help of a FEM software (Ansys Workbench 14). Physical changes of the structure such as temperature change and deformation are measured and are used as the basis for comparison between models of heat sinks. This paper also attempts to study the effect of thermal loading on the materials found in a heat sink hardware in terms of stresses that may arise due to physical restraints in the hardware as well as provide an optimized solution to reduce its form factor in order to be comparable to an Ultrabook class heat-sink. An optimized solution is made based on a cylindrical fin concept.